Associations of gestational thyrotropin levels with disease progression among pregnant women with differentiated thyroid cancer: a retrospective cohort study - Li, Xin; Fu, Peng; Xiao, Wu-Cai; Mei, Fang; Zhang, Fan; Zhang, Shanghang; Chen, Jing; Shan, Rui; Sun, Bang-Kai; Song, Shi-Bing; Yuan, Chun-Hui; Liu, Zheng (Frontiers in Endocrinology, 2024)
Purpose Pregnant women with a diagnosis of differentiated thyroid cancer (DTC) were potentially high-risk but largely ignored study population. We aimed to explore whether gestational thyrotropin levels were associated with progression of DTC. Methods We conducted a retrospective cohort study at Peking University Third Hospital in Beijing, China from January 2012 to December 2022. We included pregnant women with a pre-pregnancy DTC managed by active surveillance (under-surveillance DTC) or surgical treatment (after-surgery DTC). Dynamic changes of gestational thyrotropin levels across multiple time points were characterized by both statistical (average level, change instability, longitudinal trajectory) and clinical (thyroid dysfunction, thyrotropin suppression, and achievement of thyrotropin suppression target) indicators. Outcomes were clinician-validated progression of DTC, measured separately for patients under surveillance (tumor enlargement or lymph node metastasis) and those after surgery (≥ 3 mm growth in the size of existing metastatic foci, development of new lymph node metastases, ≥ 2 mm growth in the size of existing cancer foci in the contralateral thyroid, or biochemical progression). Results Among 43 and 118 patients with under-surveillance and after-surgery DTC, we observed no evidence of associations between any of the quantitative or clinical indicators of gestational thyrotropin levels and progression-free survival, after a median of 2.63 (IQR: 0.90-4.73) and 4.22 (2.53-6.02) year follow-up, respectively (all P values > 0.05). Conclusions Gestational thyrotropin levels appeared to play a minor role in the progression of under-surveillance or after-surgery DTC. Clinicians might focus on the risk of adverse pregnancy outcomes when optimizing thyrotropin levels for pregnant women with a diagnosis of DTC.